Pengembangan Model Pembelajaran Matematika Realistik Indonesia tentang Perbandingan di Kelas VII SMP - Husnul Laili (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
This study aims to develop a valid, practical, and effective Indonesian realistic mathematics learning model for proportions. The development of the learning kit in this study employed the model by Plump that had been modified by the product quality by Nieveen. The development of the model consisted of the preliminary investigation, design, and evaluation. The dissemination stage was not implemented in this study. The research instruments consisted of: (1) instrument evaluation sheets; (2) validation sheets; (3) learning management observation sheets; (4) student and teacher activity observation sheets; (5) student response questionnaires; and (6) learning achievement tests. Through a development process, this study produced: (1) an Indonesian realistic mathematics learning model book; (2) Indonesian realistic mathematics learning kits; and (3) research instruments. The effectiveness of the realistic mathematics learning model on the basis of: (1) the percentage of the attainment of the students’ learning mastery classically with the moderate and high mastery levels being 80% of 35 students sitting for the test; (2) the percentage of the attainment of the ideal time limit for each category of student and teacher activities; (3) the average score of the category of teachers’ ability to manage learning which was 3.54, in the moderate category; and (4) the students’ positive responses to learning components and activities.